EFFECT OF FEEDING PROPORTIONATELY MIXED MULBERRY LEAVES ON DOUBLE HYBRID SILKWORM - B. S. RATHOD,; P. K. NALWANDIKAR,; S. S. SHETGAR,; C. G. SAWANT,; M. M. SONKAMBLE, (The Bioscan, 2015)
The economic characters viz. larval weight (52.80 g), single cocoon weight (2.58 g), single shell weight (0.52 g), cocoon - shell ratio (20.15 per cent), yield/10,000 larvae brushed (23.30 kg), cocoon filament length (994.33 m), cocoon filament weight (0.31 gm), denier (2.85), lower incidence of diseases (1.66 per cent), and effective rate of rearing (98.66 per cent) of race CSR2 double hybrid silkworm were found to be superior when silkworm larvae were reared on the leaves of V1 mulberry variety. On the other hand larval weight (42.85 g), single cocoon weight (2.05 g), single shell weight (0.44 g), cocoon - shell ratio (17.05 per cent), yield/10,000 larvae brushed (19.66 kg), cocoon filament length (941 m), cocoon filament weight (0.21 gm), denier (1.99), higher incidence of diseases (5.00 per cent) and effective rate of rearing (95 per cent) were found to be inferior in case of silkworm larvae reared on the leaves of M5 mulberry variety.